Association of Bacteria and Yeasts in Hot Springs - Rikhvanov, Eugene G. (American Society for Microbiology, 1999)
The thermophilic bacterium Bacillus sp. strain TB-1 was isolated in association with the yeast Debaryomyces vanriji from hot springs at 46°C. It was shown that TB-1 excreted thiamine into the culture broth, which not only promoted D. vanriji growth in mixed culture but also increased the maximal temperature for yeast growth.